Kerja Sama Indonesia-Tiongkok Dalam Upaya Pemulihan Ekonomi Nasional Indonesia Pasca Pandemi Covid-19 - Yusuf Idrus Malik (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2022)
The COVID-19 pandemic that has occurring since 2020 has become a global challenge especially in the economic. Indonesia as the one of countries affected by this pandemic should restore the national economic condition. Indonesia decided to create PAN program and implemented by having a bilateral relationship with China to restore the economic condition. As partners for more than 70 years, China and Indonesia cooperate to restore the Indonesian economy by creating Herd immunity through vacTiongkoktion and increasing investment and export-import. This paper aims to analyse the extent of Indonesia-China bilateral relations in efforts to recover the national economy after the pandemic. By combining the concept of National Interest and the concept of Bilateral, this paper is expected to be able to answer contemporary questions and can be used as literature in developing knowledges. Keywords: COVID-19 Pandemic, Bilateral Cooperation, Economic Recovery.